LOSS OF LINEN STOCK AT RSIA PURI BUNDA: WHAT IS AFFECTING? - DRIE, IVAN -; Ratri, Devita Rahmani; Nuthea, Merry - (Fakultas Kedokteran Universitas Brawijaya)
The number of linens is insufficient, the cleanliness of the linen is lacking, and the inaccuracy of the time in linen services will affect the quality of hospital services. In addition, it has an impact on inefficient financing for linen needs and decreased patient satisfaction with linen services. Based on the results of research conducted at RSIA Puri Bunda Malang, it was found that there were still 108 linen incidents from the initial stock of linen 792. This research is a descriptive study that aims to find the root of the problem about what factors influence the loss of linen at RSIA Puri Bunda. From the results of the research conducted, there were several root problems that affected the missing linen in the inpatient unit, namely the absence of a hospital policy that regulated complete linen management techniques, weak evaluation monitoring, and inadequate linen management planning. The problem of the factors that influence the loss of linen in the inpatient unit of RSIA Puri Bunda Malang is the hospital management repairing and completing the existing linen management system or guidelines with a missing management monitoring and control system to make it more effective and efficient as well as strengthening the monitoring and evaluation functions under general manager coordination.